1999
DOI: 10.1039/a901765h
|View full text |Cite
|
Sign up to set email alerts
|

Laser ablation inductively coupled plasma mass spectrometry: achievements, problems, prospects

Abstract: Introduction ferents with isotopes of analytical interest or that are incorporated into polyatomic interferences. 2 Evolution of LA-ICP-MS 3 Laser principles Motivated partly by such difficulties, alternative sample introduction methods such as direct sample insertion (DSI),4 3.1 Ruby 3.2 Nd5YAG electrothermal vaporization (ETV),5 spark ablation (SA)6 and laser ablation (LA)7 began to be used with ICP-MS. The 3.3 Excimer 4 Laser ablation systems ability of the ICP to accept vapours and solid aerosols produced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
176
1
3

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 270 publications
(180 citation statements)
references
References 155 publications
0
176
1
3
Order By: Relevance
“…In contrast, in LA-ICPMS, it has often been demonstrated that nonmatrix-matched calibration provides accurate results in a wide variety of applications (10,11,15,17). However, because the concentration of one element in the standard and the sample must be known, the universal and routine use of this technique has been limited.…”
Section: Figures Of Meritmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, in LA-ICPMS, it has often been demonstrated that nonmatrix-matched calibration provides accurate results in a wide variety of applications (10,11,15,17). However, because the concentration of one element in the standard and the sample must be known, the universal and routine use of this technique has been limited.…”
Section: Figures Of Meritmentioning
confidence: 99%
“…However, even similar materials often exhibit different ablation rates. To avoid such a complication, an internal standard (often a minor isotope of a major element) is used, and this step has significantly improved the quality of data obtained by LA-ICPMS over the past two decades (7,10,11). However, a stoichiometric aerosol composition is still crucial for the success of quantitative analysis by LA-ICPMS.…”
Section: Quantitative Analysismentioning
confidence: 99%
“…LA-ICPMS and LA-ICP-AES are promising analytical approaches for essentially nondestructive determination of elements with very low detection limits. Variations in analytical instrumentation, as well as different chemical aspects of LA, have been discussed in many recent reviews (14)(15)(16)(17)(18)(19). In this article, we will focus on some physical aspects of the LA process that are important for microchemical analysis.…”
Section: Richard E Russo •Xianglei Mao •Samuel S Maomentioning
confidence: 99%
“…As an alternative to LIBS, LA microanalysis can work with a mass or optical spectrometer with inductively coupled plasma (ICP) as the analytical excitation source (14)(15)(16)(17)(18)(19). In this experiment, inert gases such as argon and helium are typically used to carry laser-ablated mass to the ICP excitation source.…”
Section: Richard E Russo •Xianglei Mao •Samuel S Maomentioning
confidence: 99%
“…In the LA process, a short-pulsed high-power laser beam is focused into the solid sample surface in an inert gas atmosphere (e.g. Ar) under atmospheric pressure [19]. The laser beam converts instantaneously a finite volume of the solid sample into a vapour phase aerosol, which is transferred by an Ar or He gas stream into the plasma ion source (i.e.…”
Section: Laser Ablation Inductively Coupled Plasma Mass Spectrometrymentioning
confidence: 99%